Employment Composition: A Study of Australian Employment Growth 2002-2006 - Lawson, J; Ossolinski, C (My University, 2010)
Abstract This paper uses data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey to examine whether there was a change in employment rates for people with ‘low employment’ characteristics between 2002 and 2006, which was a period of strong employment growth. In particular, it estimates the relationships between employment and personal and household characteristics using a binomial logit model, with a comparison of the coefficients in 2002 and 2006 providing tentative evidence of a broadening of employment over this period. To explore this further, the paper examines whether the broadening in employment reflects an improvement in the relative employment prospects of the unemployed or of those outside of the labour force (which includes the ‘marginally attached’ and those who can be more strictly described as being ‘not in the labour force’). Estimates of a multinomial logit model imply that the improvement in the relative employment prospects of those outside of the labour force was the more important effect. In particular, between 2002 and 2006, the concentration of ‘low employment’ characteristics decreased among people who are only marginally attached and those not in the labour force, suggesting that the strong employment growth was especially beneficial for these groups. In contrast, the concentration of ‘low employment’ characteristics in the unemployment pool was broadly unchanged.
Reserve Bank of Australia Discussion Paper,
Keywords: Employment; Labour market; Employment; Employment and unemployment